Bridging the Gaps: Future Directions for Blockchain and IoT Integration in Smart Grids - Joao C. Ferreira (Energies, 2025)
The convergence of blockchain and Internet of Things technologies holds immense promise for revolutionizing the smart grid landscape [...]